2019
DOI: 10.1002/eat.23153
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder recovery in men: A pilot study

Abstract: Objective This pilot study examined the validity of a comprehensive definition of recovery (physical, behavioral, and cognitive recovery indices) for the first time in men. Method Men with an eating disorder history were recruited from former patients at eating disorder centers, university campuses, and fitness centers/gyms. At baseline and a 12‐month follow‐up, data were collected via online surveys, diagnostic interviews, and measured weight and height from men with an eating disorder history (n = 36) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
(80 reference statements)
1
6
0
1
Order By: Relevance
“…Bardone-Cone and colleagues have published a series of studies which demonstrated that individuals who experience weight restoration and have not engaged in ED behaviours (i.e., binge eating, purging, fasting) over the past three months can be meaningfully distinguished by their scores on a measure of ED psychopathology. Specifically, individuals who reported scores within one standard deviation of community norms looked similar to individuals who have never had an ED on several measures (e.g., perfectionism, negative affect), while those with scores greater than one standard deviation above the mean looked more like individuals with a current ED on these same measures [ 5 15 ]. Research looking at clinician and lived experience definitions of recovery has found that these groups emphasize the importance of psychosocial factors, such as quality of life, relationship with food and body, and social connection (e.g., [ 16 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Bardone-Cone and colleagues have published a series of studies which demonstrated that individuals who experience weight restoration and have not engaged in ED behaviours (i.e., binge eating, purging, fasting) over the past three months can be meaningfully distinguished by their scores on a measure of ED psychopathology. Specifically, individuals who reported scores within one standard deviation of community norms looked similar to individuals who have never had an ED on several measures (e.g., perfectionism, negative affect), while those with scores greater than one standard deviation above the mean looked more like individuals with a current ED on these same measures [ 5 15 ]. Research looking at clinician and lived experience definitions of recovery has found that these groups emphasize the importance of psychosocial factors, such as quality of life, relationship with food and body, and social connection (e.g., [ 16 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a small but growing body of evidence to suggest that intuitive eating might be relevant for individuals with clinically significant eating disorders. For instance, a recent pilot study showed that men who recovered from an eating disorder reported higher levels of intuitive eating than men who were partially recovered or who had a current eating disorder (Bardone‐Cone et al, 2019). Further, another pilot study found that increases in intuitive eating during psychological treatment were associated with greater symptom improvement in patients with eating disorders (Richards, Crowton, Berrett, Smith, & Passmore, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have reported a similar pattern of results on measures of perfectionism, self-concept, coping, negative affect, negative urgency, eating expectancies, objectified body consciousness, motivation for exercise, and body appreciation and intuitive eating [ 23 31 ]. There is also preliminary evidence that this definition is valid among men [ 32 ] and predictive of sustained ‘full recovery’ status as defined by the Bardone-Cone definition [ 33 ]. It is important to note however, that all of these studies except for Bardone-Cone et al [ 32 ] were conducted in the same sample of women recruited from a child and adolescent treatment program, calling into question the generalizability of this model.…”
Section: Introductionmentioning
confidence: 99%
“…There is also preliminary evidence that this definition is valid among men [ 32 ] and predictive of sustained ‘full recovery’ status as defined by the Bardone-Cone definition [ 33 ]. It is important to note however, that all of these studies except for Bardone-Cone et al [ 32 ] were conducted in the same sample of women recruited from a child and adolescent treatment program, calling into question the generalizability of this model.…”
Section: Introductionmentioning
confidence: 99%